Molecular mechanisms of post‐burn muscle wasting and the therapeutic potential of physical exercise. Issue 2 (9th February 2023) - Dombrecht, Dorien; Van Daele, Ulrike; Van Asbroeck, Birgit; Schieffelers, David; Guns, Pieter‐Jan; Gebruers, Nick; Meirte, Jill; van Breda, Eric
Abstract: After a severe burn injury, a systemic stress response activates metabolic and inflammatory derangements that, among other, leads to muscle mass loss (muscle wasting). These negative effects on skeletal muscle continue for several months or years and are aggravated by short‐term and long‐term disuse. The dynamic balance between muscle protein synthesis and muscle protein breakdown (proteolysis) is regulated by complex signalling pathways that leads to an overall negative protein balance in skeletal muscle after a burn injury. Research concerning these molecular mechanisms is still scarce and inconclusive, understanding of which, if any, molecular mechanisms contribute to muscle wasting is of fundamental importance in designing of therapeutic interventions for burn patients as well. This review not only summarizes our present knowledge of the molecular mechanisms that underpin muscle protein balance but also summarizes the effects of exercise on muscle wasting post‐burn as promising strategy to counteract the detrimental effects on skeletal muscle. Future research focusing on the pathways causing post‐burn muscle wasting and the different effects of exercise on them is needed to confirm this hypothesis and to lay the foundation of therapeutic strategies.